The Effect of Using Iconic Gestures for Vocabulary Learning of the First Grade Students at MTs Muhammadiyah Sibatua Pangkep - Ainun, Hasri; Nurpahmi, Sitti; Rauf, Masykur (ELTIES : English Language Teaching for EFL Learners Journal, 2024)
This research aims to describe and analyze the teacher’s utterances about the code-mixing used and what factors influenced them to mix their languages. In answering these problems, researchers used a sociolinguistics approach. This research is classified as quantitative research; the data was collected by observation, documentation, and questionnaires, and analyzed using document analysis of the teacher's utterances. The researcher found, that the formulation related to type code-mixing, shows 240 code-mixed data by the teachers i.e.: insertion and alternation. The type of code-mixing most often appears on insertion was the insertion of a phrase (45.8%) followed by the insertion of the word (40.0%). Insertion of hybrid (8.3%) next, alternation (3.7%) and the last one was the insertion of repetition (2.0%). The factors that highly influence the teachers' code mixing used are bilingualism (83, 33%), vocabulary (81.25%), speaker partner (76, 04%), social community (72, 91%), situation (66,66%) and prestige (50%).